High-resolution characterization of the coagulation and drying processes of whole blood based on optical coherence tomography - Zhuo, Shufeng; Li, Meifang; Lu, Zenghai; Chen, Kaihong (Frontiers in Physics, 2023)
The escaping whole blood exhibits biochemical and physical coupled mechanisms such as coagulation and drying. In this study, a new method based on optical coherence tomography (OCT) combined speckle variance with thickness is presented for simultaneously high-resolved characteristics of coagulation and drying of whole blood during their procedure. The deep learning based on convolutional neural network (CNN) is employed for OCT image with resolution of micron order and quantitatively pixel-wise information of whole blood. Then, the pixel-wise thickness map provides high-resolved temporal-spatial dynamics of whole blood during drying procedure, and the corresponding speckle variance can uncover the information of whole blood’s coagulation. The results demonstrated that coagulation and drying of whole blood have the spatially imhomogeneous feature. This method could provide a potential for revealing couple mechanism between coagulation and drying.